Educação profissional, ensino médio e crise do capitalismo contemporâneo no Brasil - Amaral, George (Editora Oficina Universitária, 2021)
This book seeks to develop an analysis of the relationship between Work and Education, filling a gap that circumscribes Professional Education and its relationship with Secondary Education. At the turn of the millennium, the reform of vocational education took place in the midst of social struggles between classes with different societal projects, seeking to regulate the Integrated Secondary Education project. And one of the controversial issues we addressed was the government's option to carry out reforms via decrees. Another aspect concerns the complex of changes that the reforms implied, touching on the problem of the configuration of education, which is the dual character and the dichotomy that takes effect in the context of social reproduction in capitalism, with Brazilian education marked by the structural duality since the colonization process. In this context, the public school can provide propaedeutic or professional teaching, depending on which class that knowledge of both the public and private spheres is intended for. To deal with this complex debate, we turned to the classics of Marxism, with a view to revealing the appearance of the phenomenon, considering the context of the structural crisis of capital and the determinations that require new functionalities of education, mediated by public policies.